Value Conflict: Government Interests vs. User Satisfaction in E-Government - Insirat, Mutahira Nur; Haliah, Haliah; Nirwana, Nirwana (Formosa Journal of Science and Technology, 2024)
This research explores the value conflict between government interests and user satisfaction in the context of e-government. Using a Systematic Literature Review (SLR) approach, this research analyzes how user-oriented approaches can clash with established public values. The findings show that legal accountability is often prioritized by the government, overriding users' needs for more efficient and accessible services. In addition, the government's inability to accommodate inclusive user engagement, especially in digitally-disenfranchised societies, adds to the complexity of the problem. The conclusion of this study emphasizes the importance of a more collaborative approach in the design of government digital services that are not only efficient, but also able to increase inclusivity and public trust. For future research, it is recommended to focus on reducing the digital divide, improving accessibility, and exploring new technologies such as artificial intelligence and blockchain to support accountability and user satisfaction simultaneously.